1970
DOI: 10.1073/pnas.67.4.1951
|View full text |Cite
|
Sign up to set email alerts
|

Identical Linear Order of Chromosomes in Both Gametes of the Acoel Turbellarian Polychoerus carmelensis: A Preliminary Note

Abstract: Abstract. In an exceptionally well-defined first cleavage metaphase in a sectioned egg of Polychoerus carmelensis all 34 (2n) chromosomes were present in a single 8-micron section, and it was possible to identify the homologous chromosomes derived from the two parent gametes. Three groups of chromosomes from one parent, containing 7, 7, and 3 chromosomes, respectively, could be exactly matched by corresponding groups of homologues derived from the other gamete. The probability of such an ordered pattern occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

1972
1972
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 19 publications
1
15
0
1
Order By: Relevance
“…(2) The spatial organization could be newly produced in each generation if the chromosomes carry (genetical) information allowing them to become oriented in the newly constituted zygote. The observations of Costello (1970) lend indirect support to the first hypothesis. Costello found that the ordered arrangement of chromosomes in the first cleavage division of the flatworm Polychoerus carmelinis could be accounted for in terms of two identical linear arrangements of chromosomes with only minor permutations of order in one.…”
Section: The Origin Of Spatial Organizationsupporting
confidence: 58%
“…(2) The spatial organization could be newly produced in each generation if the chromosomes carry (genetical) information allowing them to become oriented in the newly constituted zygote. The observations of Costello (1970) lend indirect support to the first hypothesis. Costello found that the ordered arrangement of chromosomes in the first cleavage division of the flatworm Polychoerus carmelinis could be accounted for in terms of two identical linear arrangements of chromosomes with only minor permutations of order in one.…”
Section: The Origin Of Spatial Organizationsupporting
confidence: 58%
“…The chromosomes of the two genomes occur in blocks (Costello, 1970). Careful examination of this singular metaphase plate shows not only that the order of chromosomes within each genome is the same, but that the arms of adjacent chromosomes are roughly the same lengths.…”
Section: Proposed Model Of Interphase Chromosome Arrangementmentioning
confidence: 99%
“…Another interesting evidence showing that chromosomes have fixed location was the visualization of homologue chromosomes positioned in opposite halves of the metaphase plate. This aspect observed in early embryogenesis of a turbellarian (Costello 1970) indicated the occurrence of an ordered chromosome transmission from gametes to 286 MARIA LUIZA BEÇAK, WILLY BEÇAK and ALEXANDRE PEREIRA following generations. Non-random chromosome distribution and somatic pairing were also evidenced in uncultured cells from Chinese hamster (Juricek 1975).…”
Section: Introductionmentioning
confidence: 99%